VALIDASI MEDIA PEMBELAJARAN PPT BERBANTUAN CANVA PADA MATERI SEJARAH PERADABAN ISLAM DAULAH USMANI - Anni Wulandzari; Cindy Elvira (Al-Ihda' : Jurnal Pendidikan dan Pemikiran, 2025)
Education is the key to developing human resources and understanding history, including the discussion of Islamic civilization. The Ottoman Empire had a major impact on various fields, such as politics, social and world culture. In the digital age, education faces new challenges and opportunities, where technology enables interactive learning methods. Character education is also increasingly important for generation Z living in the era of digital environment. This study aims to develop and validate Canva-assisted PowerPoint (PPT) learning media on the material of Ottoman Islamic civilization. The method used is Research and Development (R&D) with the 4-D model (Define, Design, Develop, Disseminate). The validation results show that the learning media meets the criteria, indicating that the design, content, and usability of the media used are very suitable for improving student understanding. The use of Canva makes the learning process more interesting and interactive. This research is expected to make a significant contribution to the development of effective learning media and enrich students' learning experience of the history of Islamic civilization. Keyword: Education, PowerPoint (PPT), Canva, Research and Development (R&D).